Novel Highlight in Malarial Drug Discovery: Aspartate Transcarbamoylase - Wang, Chao; Krüger, Arne; Du, Xiaochen; Wrenger, Carsten; Groves, Matthew R. (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria remains one of the most prominent and dangerous tropical diseases. While artemisinin and analogs have been used as first-line drugs for the past decades, due to the high mutational rate and rapid adaptation to the environment of the parasite, it remains urgent to develop new antimalarials. The pyrimidine biosynthesis pathway plays an important role in cell growth and proliferation. Unlike human host cells, the malarial parasite lacks a functional pyrimidine salvage pathway, meaning that RNA and DNA synthesis is highly dependent on the de novo synthesis pathway. Thus, direct or indirect blockage of the pyrimidine biosynthesis pathway can be lethal to the parasite. Aspartate transcarbamoylase (ATCase), catalyzes the second step of the pyrimidine biosynthesis pathway, the condensation of L-aspartate and carbamoyl phosphate to form N-carbamoyl aspartate and inorganic phosphate, and has been demonstrated to be a promising target both for anti-malaria and anti-cancer drug development. This is highlighted by the discovery that at least one of the targets of Torin2 – a potent, yet unselective, antimalarial – is the activity of the parasite transcarbamoylase. Additionally, the recent discovery of an allosteric pocket of the human homology raises the intriguing possibility of species selective ATCase inhibitors. We recently exploited the available crystal structures of the malarial aspartate transcarbamoylase to perform a fragment-based screening to identify hits. In this review, we summarize studies on the structure of Plasmodium falciparum ATCase by focusing on an allosteric pocket that supports the catalytic mechanisms.